AXIT SHIKIMIC VÀ CÁC AXIT PHENOLIC PHÂN LẬP TỪ VỎ CÂY ĐỀ FICUS RELIGIOSA L. (MORACEAE) - Ính, Cẩm Thị; Quang, Trần Hồng; Hương, Hoàng Thanh; Minh, Châu Văn; Kiệm, Phan Văn (Vietnam Journal of Chemistry, 2012)
The ethyl acetate extract of the barks of Ficus religiosa L. showed moderate antioxidant activity in DPPH radical scavenging assay with SC50 value is 23.1 μg/ml. Five compounds including vanillic acid (1), 4-hydroxybenzoic acid (2), protocatechuic acid (3), gallic acid (4) and shikimic acid (5) were isolated from the barks of this plant. Their structures were identified by Mass and NMR spectra.